Checkpoint Inhibitors and Other Immune Therapies for Hodgkin and Non-Hodgkin Lymphoma - Matsuki, Eri (Curr Treat Options Oncol, 2016)
Opinion statement Treatment for relapsed/refractory (R/R) Hodgkin and non-Hodgkin lymphoma remains challenging. The introduction of rituximab to B cell non-Hodgkin lymphoma (B-NHL) treatment significantly improved patients’ response rate and survival; however, approximately one third of patients with diffuse large B cell lymphoma, the most common B-NHL subtype, still have a relapse or become refractory after first-line therapy. More recently, antibody therapies and small-molecule inhibitors were approved for treating R/R lymphomas; these agents include brentuximab vedotin, ibrutinib, and idelalisib. Immune checkpoint inhibitors and other immune therapies are emerging treatments currently being evaluated in various clinical trials for their efficacy against lymphoid malignancies. Striking results from these treatment modalities have been observed in solid tumors, and evidence is accumulating to support their use in various lymphomas. The most exciting results from immune checkpoint inhibitor therapy have been seen in patients with R/R Hodgkin lymphoma, in whom the overall response rate has reached 60–80 %. Results in NHL are more similar to those seen in other solid malignancies, ranging between 20 and 40 %, depending on the histology. Formal approval of these drugs is being awaited, as are the results of combination therapy with checkpoint inhibitors and other treatment modalities, including conventional chemotherapy, small-molecule inhibitors, and other immune therapies. Although response rates have been promising, attention must be paid to the management of unique immune-related adverse events, which warrant close monitoring in some cases. Identification of biomarkers that predict response or severe adverse events using either the tumor specimen or peripheral blood would aid in selecting patients suited for these types of treatment as well as determining the ideal sequence of treatment within the realm of immune therapies.